Assessing partially outsourced processes—lessons learned from TIPA assessments. Issue 9 (21st August 2014) - Cortina, Stéphane; Renault, Alain; Picard, Michel; Biró, M.; Messnarz, R.; Colomo‐Palacios, R.
ABSTRACT This paper presents three process assessments that took place in Luxembourg in 2012. It depicts the TIPA® process assessment framework and reports on its usage in three different partially outsourced contexts: a telecommunication service provider, a European institution, and a bank. Finally, this paper presents the lessons learned from these experimentations and some improvement perspectives. Copyright © 2014 John Wiley & Sons, Ltd.